Strengthening Prophetic Character Through Entrepreneurship Education - Winarti, Endah; Zain BSA, Fatimah; Mandasari, Susanti (International journal of technology and education research, 2024)
Entrepreneurship education has a very vital role. Spiritual-based entrepreneurship education needs to be applied in Islamic education. Sunnah as one of the main sources in Islam becomes the benchmark of Islamic education output. Prophetic character becomes an important point in Spritual-based entrepreneurship education. This study aims to examine endeavor to strengthen prophetic character in entrepreneurship education and the values instilled. Data were collected through observation, interviews, and documentation in two Pesatren involving 2 institutional leaders, 3 teachers and 4 students as source triangulation. This study shows endeavor to strengthen character include: setting vision, mission and output results oriented to mastery of the Qur'an; entrepreneurial practices that following the prophet and become economic self-reliance; Teachers provide guidance and can be a good role model of students positive character development; The material learning integrated a deepening of religious knowledge or mastery of the Qur'an, entrepreneurship and technology; learning methods develop group discussions, project based-learning and experimental, and problem solving; and periodically evaluation. While the values of prophetic character that are instilled are: Shidiq, Amanah, Tabligh, and Fathonah.